1994
DOI: 10.1113/jphysiol.1994.sp020142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of GABA and glycine depolarization‐induced calcium transients in rat dorsal horn neurons.

Abstract: 1. The mechanisms and effects of GABA-and glycine-evoked depolarization were studied in cultured rat dorsal horn neurons using indo-1 recordings of [Ca2+]i and patch clamp recordings in conventional whole-cell or perforated-patch mode.2. Application of GABA to unclamped neurons caused [Ca2+]i increases that were dose dependent and exhibited GABAA receptor pharmacology. Calcium entered the neurons via high-threshold voltage-gated calcium channels (conotoxin and nimodipine sensitive). 3. In perforated-patch reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(197 citation statements)
references
References 47 publications
(68 reference statements)
12
181
1
3
Order By: Relevance
“…In cells that have a depolarizing response to GABA, the increase is believed to result from depolarization above the level of Ca-channel activation (Marty and Llano 2005). For instance, GABA depolarized cultured rat dorsal horn neurons and produced a [Ca 2ϩ ] increase that could be prevented by removing Ca 2ϩ from the extracellular solution (Reichling et al 1994). In rat embryonic hippocampal neurons GABA induced a [Ca 2ϩ ] increase that could be removed with Ca-channel blockers (Obrietan and van den Pol 1995).…”
Section: Mechanisms Of Intracellular [Ca 2ϩ ] Increasementioning
confidence: 99%
See 1 more Smart Citation
“…In cells that have a depolarizing response to GABA, the increase is believed to result from depolarization above the level of Ca-channel activation (Marty and Llano 2005). For instance, GABA depolarized cultured rat dorsal horn neurons and produced a [Ca 2ϩ ] increase that could be prevented by removing Ca 2ϩ from the extracellular solution (Reichling et al 1994). In rat embryonic hippocampal neurons GABA induced a [Ca 2ϩ ] increase that could be removed with Ca-channel blockers (Obrietan and van den Pol 1995).…”
Section: Mechanisms Of Intracellular [Ca 2ϩ ] Increasementioning
confidence: 99%
“…In some, the GABA current reversal potentials are less negative than the resting potentials (Obrietan and van den Pol 1995;Panek et al 2002;Reichling et al 1994); in others they are closer to the resting membrane potential (Connors et al 1987). Because of this, there is some controversy about the mechanism of [Ca 2ϩ ] increase.…”
Section: Mechanisms Of Intracellular [Ca 2ϩ ] Increasementioning
confidence: 99%
“…Recent data have shown that GABA can exert a similar depolarizing action in developing neurons. This Ca 2ϩ -elevating action of GABA is not restricted to hypothalamic neurons but was found in the majority of developing neurons from eight brain regions, including hippocampus, spinal cord, cortex, olfactory bulb, and striatum (Reichling et al, 1994;Obrietan and van den Pol, 1995), and after severe neural injury . The ability of GABA to increase Ca 2ϩ levels suggests that it may have an important role during nervous system development.…”
Section: Functional Role Of Gaba-mediated Ca 2؉ Increases During Earlmentioning
confidence: 99%
“…It is widely used to study the primary afferent terminals (Brock, McLachlan, & Belmonte, 1998;Reid, Scholz, Bostock, & Vogel, 1999;Scholz, Reid, Vogel, & Bostock, 1993), soma of the sensory ganglion (Huang & Neher, 1996;Liu & Simon, 1996a;Liu, Wang, & Simon, 1996b;Todorovic & Anderson, 1990), dissociated central neurons (Reichling, Kyrozis, Wang, & MacDermott, 1994;Rusin, Jiang, Cerne, & Randic, 1993), slice preparations (Baba et al, 1998;Bao, Li, & Perl, 1998;Pan, 1998;Pan & Fields, 1996;Pan, Tershner, & Fields, 1997;Schneider, Eckert, & Light, 1998;Yoshimura & Nishi, 1993), and in vivo (Light & Willcockson, 1999). Even though cell-attached recording of an afferent terminal of corneal afferents was reported (Brock et al, 1998), this approach has been used to record ion channel activity from C-fiber axons, as well as the afferent cell body (Reid et al, 1999;Scholz et al, 1993).…”
Section: Insert Figure 4 About Here ---------------------------------mentioning
confidence: 99%